SWOT Analysis for Optimizing Competitive Strategies and Improving the Performance of PT. XYZ - Permata, Selina; Ali, Hapzi (Siber International Journal of Education Technology (SIJET), 2025)
This research focuses on the business development strategy of PT XYZ through a descriptive approach utilizing SWOT, IFAS, EFAS, and SPACE analysis methods. The analysis is conducted by identifying various internal and external factors that affect the performance of the industry within a dynamic and competitive sector. Through the SWOT approach, the strengths, weaknesses, opportunities, and threats of PT XYZ are comprehensively evaluated. Additionally, the SPACE method is used to determine the strategic position of the company within the industry. This research is expected to be beneficial for the Ministry of Agriculture and Rural Development as well as PT XYZ, to ensure a more effective environment for improving the quality of rural development. Using a qualitative descriptive approach, this study enables researchers to explore the strategies currently employed to enhance PT XYZ’s performance within a continuously changing business environment.